EARLY DIAGNOSIS AND TREATMENT OF VOGT-KOYANAGI-HARADA SYNDROME WITH OPTIC DISC SWELLING : A CASE REPORT: Poster Presentation - Case Report - Resident - Zulkarnaen Husain; Batari Todja Umar; Hasnah Eka (Majalah Oftalmologi Indonesia, 2023)
Introduction : Vogt-Koyanagi-Harada (VKH) syndrome is characterized as a multisystem autoimmune disease that affects the pigmented tissues of the eye, auditory system, skin, and central nervous system. Optic disc swelling is a common finding during the prodromal and acute uveitis stage and must be considered seriously. Case Illustration : A 41-year-old woman presented with blurred vision in both eyes in the last month, accompanied by headache, nausea, and vomiting. There is no history of penetrating ocular trauma or surgery. Examination findings for visual acuity were light perception, bilateral posterior synechia, optic disc swelling, and serous retinal detachment. A steroid injection was given due to swelling of the optic disc, and four months later, the visual acuity improved to 20/120 and 20/60, respectively, and optic disc swelling and serous retinal detachment decreased. Discussion : In the acute uveitic stage, VKH can be presented with bilateral optic disc edema and various degrees of serous retinal detachment. The key to the management of VKH is early diagnosis and systemic corticosteroid in the acute uveitis stage, otherwise, improper and inadequate treatment can lead to chronic recurrent VKH disease. Our patient presented with acute uveitis and was treated promptly and adequately. Conclusion : Optic disc swelling may occur in VKH and worsen the visual prognosis, early diagnosis and treatment of VKH syndrome focused on optic disc swelling can improve the visual prognosis.